Pellagra secondary to selective eating in a child with autism. Issue 4 (23rd April 2020) - Zaenglein, Andrea; Martin, Ashley; Carlson, Lisa; Williams, Keith E.
Abstract: Once a significant cause of morbidity and mortality, health care providers rarely see primary pellagra in developed countries where fortification of foods with niacin is commonplace and niacin‐rich foods are generally widely available. We report a ten‐year‐old boy with autism spectrum disorder who presented with photosensitive dermatitis which resolved after vitamin supplementation and dietary changes. In this child, the pellagra developed as the result of a long‐term pattern of selective eating. Restricted diets, even to the point of nutrient deficiencies, are well‐documented among children with autism spectrum disorders (ASD).